A comparison of methodologies of brief functional analysis. (August 2015) - Badgett, Natalie; Falcomata, Terry S.
Abstract Objective: To evaluate correspondence between three models of brief functional analysis (BFA); to evaluate a latency-based model of BFA. Methods: Single subject research; three models of BFA; latency-based BFA; brief A-B model with programmed antecedents and no programmed consequences for aberrant behaviour; A-B-C model with programmed antecedents and programmed consequences for aberrant behaviour; contingency reversal treatment evaluations conducted with each model; each model implemented with four individuals with autism diagnoses; correspondence of results between the three BFA models in terms of the conditions in which aberrant behaviour occurred. Results: Overall, strong correspondence between all three BFA models was observed; several specific instances of non-correspondence within participants observed; more differentiation observed between test and control conditions in A-B model than A-B-C model. Conclusions: Additional support that clinicians and educators have flexibility in choosing BFA model that fits the specific, idiosyncratic variables and constraints of their setting (e.g. outpatient; classroom) and client(s).